Structure and Growth of Hexagonal Boron Nitride on Ir(111) - Farwick zum Hagen, Ferdinand H; Zimmermann, Domenik M; Silva, Caio C; Schlueter, Christoph; Atodiresei, Nicolae; Jolie, Wouter; Martínez-Galera, Antonio J; Dombrowski, Daniela; Schröder, Ulrike A; Will, Moritz; Lazić, Predrag; Caciuc, Vasile; et al. (ACS nano, 2016)
Using the X-ray standing wave method, scanning tunneling microscopy, low energy electron diffraction, and density functional theory, we precisely determine the lateral and vertical structure of hexagonal boron nitride on Ir(111). The moiré superstructure leads to a periodic arrangement of strongly chemisorbed valleys in an otherwise rather flat, weakly physisorbed plane. The best commensurate approximation of the moiré unit cell is (12 × 12) boron nitride cells resting on (11 × 11) substrate cells, which is at variance with several earlier studies. We uncover the existence of two fundamentally different mechanisms of layer formation for hexagonal boron nitride, namely, nucleation and growth as opposed to network formation without nucleation. The different pathways are linked to different distributions of rotational domains, and the latter enables selection of a single orientation only.